2006
DOI: 10.1083/jcb.200512136
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint silencing during the DNA damage response in Caenorhabditis elegans embryos

Abstract: In most cells, the DNA damage checkpoint delays cell division when replication is stalled by DNA damage. In early Caenorhabditis elegans embryos, however, the checkpoint responds to developmental signals that control the timing of cell division, and checkpoint activation by nondevelopmental inputs disrupts cell cycle timing and causes embryonic lethality. Given this sensitivity to inappropriate checkpoint activation, we were interested in how embryos respond to DNA damage. We demonstrate that the checkpoint re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 40 publications
8
75
1
Order By: Relevance
“…This is consistent with a previous study that found that nonhomologous end-joining is important in non-cycling somatic cells [13]. While our experiments cannot distinguish between germs cells and early embryos, such experiments would be interesting given the fact that cell cycle checkpoint activation is silenced in C. elegans in early embryos, but not in the germline [12]. Importantly, we previously showed that there was no detectable difference in UVC damage repair kinetics between wild-type and glp-1 nematodes when measured in starved L1s, prior to germ cell proliferation [23].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a previous study that found that nonhomologous end-joining is important in non-cycling somatic cells [13]. While our experiments cannot distinguish between germs cells and early embryos, such experiments would be interesting given the fact that cell cycle checkpoint activation is silenced in C. elegans in early embryos, but not in the germline [12]. Importantly, we previously showed that there was no detectable difference in UVC damage repair kinetics between wild-type and glp-1 nematodes when measured in starved L1s, prior to germ cell proliferation [23].…”
Section: Discussionsupporting
confidence: 92%
“…One possibility to be explored is that KO embryos have an increased sensitivity to DNA damage, thus in many cases they do not survive up to the larval stages. This hypothesis fits with the notion that DNA-damage-induced checkpoint is silenced during early stages of embryo development (30) to ensure that cell cycle progression is not hampered by DNA damage. In the Fe65;Fe65L1 double KO mice the phenotype observed (23), mainly characterized by focal heterotopias of neurons likely due to the pial basement membrane disruption and intriguingly similar to that observed in APP;APLP1;APLP2 mice (24), is very likely due to the impairment of an unknown Fe65 function different from that responsible for the phenotype we are describing.…”
Section: Discussionsupporting
confidence: 54%
“…A tendency of dose-response in the developmental delay was observed only in the early developmental stage, which might suggest that the time allowed for repair processes in the middle and late developmental stages was fixed and independent of damage level. In many organisms, including C. elegans , D. melanogaster and Xenopus laevis , early embryogenesis is characterized by rapid progression through the cell cycle [28], [29]. Adherence to the schedule during the initial stage of development (until mid-blastula) seems to be very important for survival of the embryo, and it is programmed by specific signals during development (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, if DNA is damaged during embryo gastrulation (where the G2 phase has been added into cell cycles) it results in a checkpoint-dependent delay of entry into mitosis [30]. Also in the early and fast developing embryos of C. elegans DNA damage does not inhibit the cell cycle, and this has been suggested as a mechanism (TLS based) allowing the embryo to survive even when their chromosomes are highly damaged [28]. From the perspective of the radiation tolerance in tardigrades, and also from the fact that tardigrades, nematodes and arthropods belong to the protostome superclade Ecdysozoa it will be of considerable interest to investigate the developmental processes in tardigrades, in particular the checkpoint and DNA repair system.…”
Section: Discussionmentioning
confidence: 99%